2021
DOI: 10.3389/fphys.2021.620608
|View full text |Cite
|
Sign up to set email alerts
|

Irisin: A New Code Uncover the Relationship of Skeletal Muscle and Cardiovascular Health During Exercise

Abstract: Exercise not only produces beneficial effects on muscle itself via various molecular pathways, but also mediates the interaction between muscles and other organs in an autocrine/paracrine manner through myokines, which plays a positive role in maintaining overall health. Irisin, an exercise-derived myokine, has been found involved in the regulation of some cardiovascular diseases. However, the relationship between irisin and cardiovascular health is not fully elucidated and there are some divergences on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 103 publications
(184 reference statements)
1
26
0
Order By: Relevance
“…This hypothesis is supported by both in vivo and in vitro experiments that showed that GTPase OPA1, which is responsible for the regulation of mitochondrial dynamics and is crucial for adapting mitochondrial function and preserving cellular health, is downregulated in the infarcted heart, whereas irisin treatment upregulated its expression and protected cardiomyocytes from further damage after myocardial infarction [135]. Collectively, these results seem to indicate that irisin serves as a novel approach to elicit cardioprotection, which is associated with improved mitochondrial function [136]. Furthermore, serum irisin concentrations are reported to be inversely associated with the prevalence of coronary artery calcification after adjustment for age and behavioral factors.…”
Section: Irisinmentioning
confidence: 77%
“…This hypothesis is supported by both in vivo and in vitro experiments that showed that GTPase OPA1, which is responsible for the regulation of mitochondrial dynamics and is crucial for adapting mitochondrial function and preserving cellular health, is downregulated in the infarcted heart, whereas irisin treatment upregulated its expression and protected cardiomyocytes from further damage after myocardial infarction [135]. Collectively, these results seem to indicate that irisin serves as a novel approach to elicit cardioprotection, which is associated with improved mitochondrial function [136]. Furthermore, serum irisin concentrations are reported to be inversely associated with the prevalence of coronary artery calcification after adjustment for age and behavioral factors.…”
Section: Irisinmentioning
confidence: 77%
“…Since then, many beneficial roles have been ascribed to it. For instance, as an important regulator of energy metabolism, irisin plays a protective role against type 2 diabetes mellitus and obesity [2,3]; maintains cardiovascular health [4]; acts as a behavioural antidepressant in mood regulation [5], and protects against bone loss and muscle atrophy [6]. Irisin has also been linked to the increased expression of brain-derived neurotrophic factor (BDNF) with subsequent beneficial effects on brain health and cognitive function [7].…”
Section: Background Description Of the Conditionmentioning
confidence: 99%
“…Irisin is an exercise-induced myokine that is cleaved from the transmembrane protein fibronectin type III (FNIII) domain-containing protein 5 (FNDC5) expressed in myocytes and may link the cardiovascular-skeletal muscle axis ( Ma et al, 2021 ). Despite the role of FNDC5 as the precursor of irisin, FNDC5 could also act as the receptor of irisin based on its fibronectin type III domain containing the Arg-Gly-Asp (RGD) sequence ( Main et al, 1992 ; Teufel et al, 2002 ; Erickson, 2013 ), which might mediate the autocrine or endocrine action of irisin.…”
Section: Introductionmentioning
confidence: 99%